Access to acute care resources in various income settings to treat new-onset stroke: A survey of acute care providers - Ramadhan Chunga (African Journal of Emergency Medicine, 2019)
Introduction: Stroke affects 15 million people annually and is responsible for 5 million deaths per annum globally. In contrast to the trend in low- and middle-income countries (LMICs), stroke mortality is on the decline in high-income countries (HICs). Even though the availability of resources varies considerably by geographic region and across LMICs and HICs, evidence suggests that material resources in LMICs to implement recommendations from international guidelines are largely unmet. This study describes and compares the availability of resources to treat new-onset stroke in countries based on the World Bank’s gross national incomes, using recommendations of the American Heart Association and the American Stroke Association 2013 update. Methods: A self-reported cross-sectional survey was conducted of delegates that attended the April 2016 International Conference on Emergency Medicine using the web-based e-Survey client, Survey Monkey Inc. The survey assessed both pre-hospital and in-hospital settings and was piloted before implementation. Results: The survey was distributed and opened by 955 delegates and 382 (40%) responded. Respondents from LMICs reported significantly less access to a prehospital service (p < 0.001) or a national emergency number (p < 0.001). Access to specialist neurology services (p < 0.001) and radiology services (p < 0.001) were also significantly lower in LMICs. Conclusion: The striking finding from this study was that there was essentially very little difference between the responses between LMIC and HIC respondents with a few notable exceptions. The findings also propose a universal lack of adherence to the 2013 AHA/ASA stroke management guideline by both groups, in contrast to the good reported knowledge thereof. Carefully planned qualitative research is needed to identify the barriers to achieving the 2013 AHA/ACA recommendations. Keywords: Emergency, Low resource, Access, Stroke, Cerebrovascular accident